University – Industry Cooperation in Central and Eastern Europe: A Common Past, a Different Future? - Cristina Serbanica; Gabriela Dragan (CES Working Papers, 2012)
The aim of this paper is to map the position of the Central and Eastern Europe (CEE) region for university – industry cooperation in research and development. (R&D) To meet this goal, we use the Global Competitiveness Index 2011 database and consider those indicators describing the knowledge production and the knowledge absorption potential of 142 participating countries. Based on a discriminant analysis, we classify the countries and synthesize their performances for the selected indicators. The results confirm our hypothesis regarding the heterogeneity of the CEE countries' performances for university – industry cooperation and identifies the factors that explain the variations.
Keywords: O3; 330; university – industry cooperation; CEE region; Global Competitiveness Index 2011; discriminant analysis Romania